Antonin Scalia and American constitutionalism : the historical significance of a judicial icon - Purcell, Edward A. (New York : Oxford University Press, 2020)
Antonin Scalia and American Constitutionalism is a critical study of Justice Antonin Scalia's jurisprudence, his work on the U.S. Supreme Court, and his significance for an understanding of American constitutionalism. After tracing Scalia's emergence as a hero of the political right and his opposition to many of the decisions of the Warren Court, this book examines his general jurisprudential theory of originalism and textualism, arguing that he failed to produce either the objective method he claimed or the "correct" constitutional results he promised. The book argues that Scalia applied his jurisprudential theories in inconsistent ways and often ignored, twisted, or abandoned the interpretive methods he proclaimed, in most cases reaching results that were consistent with "conservative" politics and the ideology of the post-Reagan Republican Party.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 28, 2020).
Keywords: Scalia, Antonin, -- 1936-2016 -- Influence; United States. -- Supreme Court; Constitutional law -- United States; Law; Laws of specific jurisdictions & specific areas of law